On infinite dimensional Volterra type operators - Mukhamedov, Farrukh; Saburov, Mansoor (Eudoxus Press, LLC, 2009)
In this paper we study Volterra type operators on infinite dimensional simplex. It is provided a sufficient condition for Volterra type operators to be bijective. Furthermore it is proved that the condition is not necessary.